2019
DOI: 10.1039/c8nh00172c
|View full text |Cite
|
Sign up to set email alerts
|

Tin sulfide modified separator as an efficient polysulfide trapper for stable cycling performance in Li–S batteries

Abstract: Lithium–sulfur batteries (Li–S) are considered the most promising systems for next-generation energy storage devices due to their high theoretical energy density and relatively low cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(58 citation statements)
references
References 48 publications
0
58
0
Order By: Relevance
“…Brindha et al have reported a separator modified with SnS 2 nanosheets and used in LSB. [17] Gao et al enhanced the adsorption effect of polysulfides and catalyzed the transformation of polysulfides through cobalt-doped SnS 2 . [18] However, SnS 2 is a semiconductor material with a wide band gap and poor conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Brindha et al have reported a separator modified with SnS 2 nanosheets and used in LSB. [17] Gao et al enhanced the adsorption effect of polysulfides and catalyzed the transformation of polysulfides through cobalt-doped SnS 2 . [18] However, SnS 2 is a semiconductor material with a wide band gap and poor conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Finally,t he preparationo ft he 2D functional separator usually appliesf iltration, whichw ould reduce the industrial production in the future.M ore facile and scalable methods still require exploration. [43] 480 mAh g À1 at 0.67 C800 mAh g À1 after 300 cycles at 100 mA g À1 MoS 2 /3 Dg raphene [46] 600 mAh g À1 at 3Ag À1 689 mAh g À1 after 200 cycles at 0.5 Ag À1 MoS 2 /rGO [47] 615 mAh g À1 at 2C 368 mAh g À1 after 500 cycle at 1C 3D MoS 2 [49] 756 mAh g À1 at 3C 593 mAh g À1 after 600 cycles at 1C MoS 2 -PDDA-PAA [56] 766 mAh g À1 at 3C 423 mAh g À1 after 2000 cycles at 1C Thermals tability (150 8C) Sb 2 S 3 /CNT [55] 530 mAh g À1 at 2C 450 mAh g À1 after 200 cycles at 2C 1.33-2.14 eV binding energy with PS SnS 2 -modified separator [54] 700 mAh g À1 at 5C 597 mAh g À1 after the 500 cycles at 2C [28] 281.8 h, 0.2 mA cm À2 11.8 h, 0.2 mA cm À2 3D conformalGOc oated GF [29] % 320 h, 1mAcm À2 , 1mAh cm À2 % 80 h, 1mAcm À2 , 1mAh cm À2 83 %e fficiency,160 cycles, 1mAcm À2 ,1mAh cm À2 80 %e fficiency,80cycles, 1mAcm À2 ,1mAhcm À2 GO-SiO 2 coated polyolefin [30] 350 cycles( LiCoO 2 cathode, 1C)2 20 cycles N, Sd opedgraphene coated PE [32] 85 %, 350 cycles( LiNi 0.8 Co 0.15 Al 0.05 O 2 cathode,0 .5 C)…”
Section: Discussionmentioning
confidence: 99%
“…Sb 2 S 3 and SnS 2 were also explored as interlayer and functional additives. [54] Benefiting from the 2D structure, researchers appliedt he electrochemical lithium (EC-Li)e xfoliation strategy to construct an ultrathin Sb 2 S 3 nanosheet interlayer to achieve remarkable rate stability (450 mAh g À1 after 200 cycles at a high current density of 2C) ( Figure 4d). [55] The moderate binding energy between Sb 2 S 3 and PS also contributed to this improvedi nterlayer (Figure 5c).…”
Section: Functional Interlayers and Separator-additives During The Elmentioning
confidence: 99%
“…Moreover, Kim group fabricated a SnS 2 -modified separator to facilitate the redox reaction of LiPS [ 133 ]. SnS 2 is a conductive, polar, and catalytic material used in the conversion reaction of LiPS.…”
Section: Real Cases Of Modifying Separators For Li-metal Based Batmentioning
confidence: 99%